Pericardial window as a surgical method for preventing significant postoperative pericardial effusion - K. S. Kiryakov; A. R. Zakiryanov; T. A. Khalilulin; N. Y. Zakharevich; O. A. Pozdnyakov; А. M. Goltz; D. S. Ivanov; A. A. Sukhachev; V. M. Zakharevich (Вестник трансплантологии и искусственных органов)
Postoperative pericardial effusion (PPE) represents a very common complication in cardiac surgery. Accumulation of a significant amount of free fluid in the pericardial cavity is a multifactorial process. Identifying the cause is not always possible. This complication occurs more frequently in patients after heart transplantation than in patients who underwent reconstructive cardiac surgery. Having hemodynamically significant effusion requires surgical evacuation of fluid from the pericardial cavity. This can affect the postoperative period and increase the length of stay at the hospital. For this reason, developing and ensuring widespread use of methods for prevention of this complication are urgent and relevant tasks.